Implementasi Program Kartu Identitas Anak (KIA) di Dinas Kependudukan dan Pencatatan Sipil Kota Bukittinggi - Armi Mahtadea Mufti; Desna Aromatica; Nila Wahyuni (Indonesian Journal Publisher, 2025)
This study aims to describe the Implementation of the Child Identity Card (KIA) Program at the Population and Civil Registration Office of Bukittinggi City. KIA is implemented based on the Regulation of the Minister of Home Affairs Number 2 of 2016 concerning Child Identity Cards. In the implementation, there are stakeholders involved, namely schools, LPKA Class II Payakumbuh in Tanjung Pati, and Bukittinggi City Hospital. This study was analyzed using the implementation theory according to Donald Van Meter and Carl Van Horn. The research method used is descriptive qualitative, with data collection techniques through interviews and documentation. Then the data validity technique uses source triangulation. The results of the study indicate that the Implementation of the Child Identity Card (KIA) Program at the Population and Civil Registration Office of Bukittinggi City has not run optimally. As the indicator of justice in the effort to pick up the ball to school has not been carried out evenly in Bukittinggi City, human resources in terms of quantity are inadequate, there is still a lack of budget, and the existence of facilities that are in a damaged condition, less supportive social conditions, and constraints on economic conditions.